En bloc kidney transplant from an 18-month-old donor to an adult recipient: Case report and literature review() - Mwipatayi, B. Patrice (Elsevier, 2013)
INTRODUCTION: There is an ever-increasing need for organ donations globally. Paediatric kidney transplantation into adult recipients is a well-recognised technique to expand the donor pool. The transplantation can be done either via en bloc kidney transplant (EBKT) or as single kidney transplantation (SKT). PRESENTATION OF CASE: An EKBT from a 18-month-old (15 kg) male patient was transplanted in a 35-year old, 85 kg male with end stage renal failure (ESRF), secondary to Focal Segmental Glomerulosclerosis (FSGS) on haemodialysis. Post-operative recovery was uneventful. Immuno-suppressant drugs used were tacrolimus, basiliximab and prednisolone. Doppler ultrasound scans performed post-operatively showed normal renal resistive indices in both kidneys. Serum creatinine decreased from 1200 to 170 μmol/L 57 with eGFR improving from 4 to 38 mL/min/1.73 m(2) at four weeks post-transplant. DISCUSSION: Given the low incidence of paediatric donors, EBKTs are relatively uncommon and subsequently published series tend to be centre specific with small numbers. The graft survival rates tell us that paediatric kidney donors should not be considered as marginal transplants. The difficulty is in determining when it is more appropriate to perform a paediatric EBKT as opposed to splitting and performing two SKT. Unfortunately there are no widely accepted guidelines to direct clinicians. CONCLUSION: This case report highlights the first EKBT performed at our institution. The current literature demonstrates that paediatric donors are excellent resources that should be procured whenever available.